2021
DOI: 10.1038/s41388-021-01948-6
|View full text |Cite|
|
Sign up to set email alerts
|

The ELF3-regulated lncRNA UBE2CP3 is over-stabilized by RNA–RNA interactions and drives gastric cancer metastasis via miR-138-5p/ITGA2 axis

Abstract: LncRNAs play essential roles in tumorigenesis and tumor progression. Pseudogene UBE2CP3 is an antisense intronic lncRNA. However, the biological function of UBE2CP3 in gastric cancer (GC) remains unknown. In this study, we revealed that lncRNA UBE2CP3 was aberrantly upregulated in multiple independent gastric cancer cohorts, and its overexpression was clinically associated with poor prognosis in GC. UBE2CP3 was mainly located in cytoplasm and promoted migratory and invasive capacities of GC cells in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Recent studies have shown that lncRNAs regulate many important cancer phenotypes through controlling different cancer-related pathways [ 31 , 32 ]. For example, Li et al reported that lncRNA UBE2CP3 targets miR-138-5p to regulate gastric cancer progression via EMT process [ 33 ]. In this research, we demonstrated that lncRNA RP11-89 could play a regulatory role in bladder cancer ferroptosis and progression directly via a novel ceRNA network of RP11-89/miR-129-5p/PROM2 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that lncRNAs regulate many important cancer phenotypes through controlling different cancer-related pathways [ 31 , 32 ]. For example, Li et al reported that lncRNA UBE2CP3 targets miR-138-5p to regulate gastric cancer progression via EMT process [ 33 ]. In this research, we demonstrated that lncRNA RP11-89 could play a regulatory role in bladder cancer ferroptosis and progression directly via a novel ceRNA network of RP11-89/miR-129-5p/PROM2 axis.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been widely proved that there is a close connection between lncRNAs and gastric cancer metastasis. Some of them are reported to promote the metastasis of gastric cancer, such as lncRNA UBE2CP3, HOTAIR and GMAN (Wei et al, 2020; Xu et al, 2020 ; Li et al, 2021 ). Meanwhile, lncRNAs such as lnc-CTSLP4 and lnc-LEMGC can inhibit the metastasis of gastric cancer through different ways ( Pan et al, 2021 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previously published study had implied that transcription factor ELF3 plays tumor-suppressive roles in GC. (11,13) Herein, we further con rmed that ELF3 protein and ELF3 mRNA were signi cantly downregulated in GC (Fig. 3H-J).…”
Section: Exploration Of Lncrnas Regulated By Transcription Repressor ...mentioning
confidence: 52%
“…(31) Similarly, Li et al have reported that the antisense intronic lncRNA UBE2CP3 and IGFBP7 mRNA can form an RNA duplex, which could strengthen UBE2CP3 mRNA stability in GC. (11) Herein, we also found that the rst exon of ELF3-AS1 could bind with the overlapping regions of the rst exon of ELF3-201 transcripts to form double-stranded RNA molecules, which interacted with ILF2/ILF3 complex. However, whether the ILF2/ILF3 complex can regulate the SNAI2 signaling by regulating the stability of ELF3-AS1 transcripts remains to be further studied.…”
Section: Discussionmentioning
confidence: 69%